2019
DOI: 10.1002/hyp.13553
|View full text |Cite
|
Sign up to set email alerts
|

Clogging process by suspended solids during groundwater artificial recharge: Evidence from lab simulations and numerical modelling

Abstract: Permeability reduction of infiltration media due to suspended solid (SS) clogging is the bane of groundwater artificial recharge. To overcome the clogging problem and advance the understanding of the process-based spatial-temporal evolution of SS clogging, a 1D laboratory column simulation was carried out, followed by numerical modelling of the experimental data in this study. It was found that clogging caused a reduction in the hydraulic conductivity (K) in the upper layer at the beginning and extended deeper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…In a more specific application to porous-media system, Wang and Sun (2018) operations. This observation will also be validated in the proposed dynamical rapid filtration model (DRFM) later in this thesis study and has also been confirmed in most recent studies (Chu et al, 2019). In their subsequent work (Dalwadi et al, 2016), the authors built upon their previous model (Dalwadi et al, 2015) to account for the clogging effects by assuming a first-order reaction mechanism on the surface of a • First few researchers who rigorously derived analytical functions, via the homogenization theory with multiscale perturbation analysis, to analyse complex fluid and mass transport problems in porous media domains…”
Section: Homogenization Theory Coupled With Multiscale Perturbation Asupporting
confidence: 81%
“…In a more specific application to porous-media system, Wang and Sun (2018) operations. This observation will also be validated in the proposed dynamical rapid filtration model (DRFM) later in this thesis study and has also been confirmed in most recent studies (Chu et al, 2019). In their subsequent work (Dalwadi et al, 2016), the authors built upon their previous model (Dalwadi et al, 2015) to account for the clogging effects by assuming a first-order reaction mechanism on the surface of a • First few researchers who rigorously derived analytical functions, via the homogenization theory with multiscale perturbation analysis, to analyse complex fluid and mass transport problems in porous media domains…”
Section: Homogenization Theory Coupled With Multiscale Perturbation Asupporting
confidence: 81%
“…In this study, chemical and mechanical stability properties on materials improved through epoxy resin mixtures with CNS (Epoxy-CNS) to manufacture thin filtration coatings for water treatment purposes. These composite coating materials were designed for agricultural irrigation water cleaning and reuse systems in order to remove suspended solids and fine particles which are undesirable due to clogging of irrigation systems [40].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods for clogging assessment are used: suspended solid clogging during laboratory soil column tests was assessed by numerical spatial-temporal modeling [7]; physical clogging of a one-dimensional gravel filter column under both constant and variable water levels was quantified for different sediment inflow concentrations [8]; the wastewater effluent clogging effect on structured silty clay loam subsoil was investigated by pilot-scale infiltration cells in different compositions and loading rates [9]. It was found that soil clogging development correlates with the mass density cumulative loadings, indicated by total biochemical oxygen demand and suspended solids.…”
Section: Introductionmentioning
confidence: 99%